1995
DOI: 10.2134/jeq1995.00472425002400010025x
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Cadmium and Zinc with Application to Soil Solutions

Abstract: A two‐part method has been developed for determination of Cd and Zn species in 50‐mL soil solution samples containing low concentrations of Cd and Zn (1–10 μg Cd L−1 and 50–1000 μg Zn L−1). The method uses two cation exchange resins (Amberlite CG 120 and Chelex 100) in a batch‐column‐batch procedure and relies on analytical determinations of Cd and Zn by graphite furnace atomic absorption spectrophotometry. The first part (batch) of the method allows determination of free divalent Cd2+ and Zn2+. This part is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 0 publications
2
80
0
1
Order By: Relevance
“…Cu and Pb have higher affinity for DOM and therefore a very small fraction of these metals exists as free hydrated metal ions in soil solution (Aualiitia and Pickering, 1986;Sauvé et al, 1998;Weng et al, 2001b). On the other hand, metals such as Cd, Ni and Zn are less prone to form such stable metal-organic complexes (Aualiitia and Pickering, 1986;Pinheiro et al, 1994;Holm et al, 1995). Thus, a larger fraction of these metals is recovered as free hydrated metal ions.…”
Section: Tablementioning
confidence: 99%
“…Cu and Pb have higher affinity for DOM and therefore a very small fraction of these metals exists as free hydrated metal ions in soil solution (Aualiitia and Pickering, 1986;Sauvé et al, 1998;Weng et al, 2001b). On the other hand, metals such as Cd, Ni and Zn are less prone to form such stable metal-organic complexes (Aualiitia and Pickering, 1986;Pinheiro et al, 1994;Holm et al, 1995). Thus, a larger fraction of these metals is recovered as free hydrated metal ions.…”
Section: Tablementioning
confidence: 99%
“…Soil solution samples were collected from the extra control and EDTA pots 6, 12, 29 and 52 days after the EDTA was applied to the soil. Each soil solution sample was separated into several aliquots for analysis of pH, total organic carbon (TOC) content, and total and organic chelate combined Cu, Zn, Pb and Cd complexes concentrations by the methods of Holm et al (1995). The aboveground parts of Indian mustard were washed with tap water and rinsed with distilled water, oven dried at 80 • C, ground and digested with 3:2 (v/v) nitric/perchlolic acids.…”
Section: Pot Experimentsmentioning
confidence: 99%
“…Fotovat and Naidu (1997) reported favorable results when using cation exchange resin for speciation of zinc (Zn 2+ ) and copper (Cu 2+ ) compared to a geochemical model named MINTEQA2. Holm et al (1995) concluded, in a study on speciation of cadmium and zinc in soil solutions, that the ion exchange method determines the dissolved species experimentally with minimal changes in the sample composition, and thus is able to work in complex solutions with ill-defined organic ligands.…”
Section: Ion Speciation In Soil Environmentsmentioning
confidence: 99%